MIDDLE TRIASSIC ECHINODERMS FROM THE SAN SALVATORE FORMATION OF LOMBARDY (ITALY) AND CANTON TICINO (SWITZERLAND) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
An echinoderm fauna from the San Salvatore Formation (Middle Triassic, Southern Alps) is here  described in detail for the first time. Identifiable crinoids and echinoids were collected from three different localities: Mt. San Salvatore (Ticino, Switzerland), Rasa di Varese and San Michele (Lombardy, Italy). Crinoid taxa include Encrinus cf. aculeatus, Holocrinus sp. indet., Zardinicrinus cf. granulosus, Encrinidae gen. et sp. indet. Echinoid taxa include “Cidaris” cf. roemeri, Serpianotiaris sp. indet., Triadocidaris transversa, Triadocidaris sp. indet., and an indetermined form (Cidaridae). Most of the material was collected from Rasa di Varese, along with a rich upper Anisian ammonoid and conodont fauna, belonging to the upper Reitzi Zone and the Secedensis Zone. Migration of crinoids have been documented during the upper Anisian (from upper Pelsonian to lower Illyrian), mainly from the westernmost Tethyan Realm northward to the Germanic basin. Crinoid taxa already reported in the lower and upper Illyrian of the Germanic basin have also been collected, dated here to the late Illyrian (upper Reitzi Z.-Secedensis Z.) suggesting that several taxa migrated southwards in the Tethys realm during the late Illyrian.
Keywords: Crinoidea; Echinoidea; Anisian; Illyrian; carbonate platform; palaeoecology; Tethys; Southern Alps